Hukum dan Globalisasi terhadap Perlindungan Hak Cipta dalam Media Elektronik Al-Qur’an - Marsella, Marsella; Azwar, Tengku Keizerina Devi (Universitas Medan Area, 2023)
This research aims to examine the relationship between law, globalization and copyright protection in the context of the electronic media of the Koran. This research also wants to know the challenges and solutions faced in protecting the copyright of the Al-Qur'an in the digital era. This research uses a qualitative approach with a literature study method. Data is collected from various sources, such as books, journals, articles, laws and official documents. The data was then analyzed using content analysis techniques. This research found that copyright of the Al-Qur'an in electronic media is different from copyright of other works, both from a legal, ethical and religious perspective. Globalization affects the copyright protection of the Qur'an in electronic media by providing global standards, international agreements, and legal challenges. The electronic media of the Koran has special characteristics that require copyright protection in accordance with Islamic principles. Copyright protection of the Koran.